THE SYNTHETIC BIOACTIVE CALCIUM-PHOSPHATE MINERAL COATING INFLUENCE ON THE PERI-IMPLANT ZONE BONE TISSUE - Alexander Anatolievich Markov; Andrey Aleksandrovich Ponomarev; Mikhail Dmitrievich Zavatsky; Anna Nikolaevna Kurchatova; Konstantin Sergeevich Sergeev; Alexander Anatolyevich Sokolyuk (Современная наука и инновации, 2022)
It is presented the results of the in vivo experiment in which the main bone strength parameters of the peri-implant zone with the use of titanium implants with synthetic bioactive calcium-phosphate mineral coating and titanium implants without bioactive coverage analysis is conducted. The achieved results lead us to a conclusion that the bone tissue peri-implant zone reaction to titanium implants with a synthetic bioactive calcium-phosphate mineral coating decreases, which will ensure the preservation of bone tissue strength in the peri-implant zone at a high level.